An Open-Label, Randomized, Active-Controlled Trial of 8 Versus 12 Weeks of Elbasvir/Grazoprevir for Treatment-Naive Patients With Chronic Hepatitis C Genotype 1b Infection and Mild Fibrosis (EGALITE Study): Impact of Baseline Viral Loads and NS5A Resistance-Associated Substitutions. (8th April 2019) - Huang, Chung-Feng; Hung, Chao-Hung; Cheng, Pin-Nan; Bair, Ming-Jong; Huang, Yi-Hsiang; Kao, Jia-Horng; Hsu, Shih-Jer; Lee, Pei-Lun; Chen, Jyh-Jou; Chien, Rong-Nan; Peng, Cheng-Yuan; Lin, Chun-Yen; et al.
Abstract: Background: A 12-week grazoprevir/elbasvir regimen is highly effective against hepatitis C virus genotype 1 (HCV-1) infection. The efficacy of an 8-week regimen for treatment-naive HCV-1–infected patients with mild fibrosis has not been determined. Methods: Treatment-naive HCV-1b–infected patients with mild fibrosis were randomly assigned to receive 8 (n = 41) or 12 (n = 41) weeks of grazoprevir/elbasvir therapy. The primary end point was a sustained virologic response, defined as an HCV RNA level of < 12 IU/mL, at posttreatment week 12 (SVR12). Results: SVR12 was achieved by 87.8% of patients (36 of 41) in the 8-week arm and 100% (41 of 41) in the 8-week arm of the full-analysis population and by 90.0% (36 of 40) and 100% (41 of 41), respectively, in the per-protocol population (all P = .055). In the 8-week arm, a significantly lower SVR12 rate was observed among patients with a high HCV-1b load, defined as ≥1 500 000 IU/mL (79% vs 100%; P = .042), and among those with a baseline Y93H resistance-associated substitution (RAS) frequency of >15% in HCV nonstructural protein 5A (NS5A; 40.0% vs 97.1%; P = .004). Between-group analysis demonstrated that, among patient with a high HCV-1b load and a baseline Y93H RAS frequency of >15%, those in the 8-week arm had a substantially lower SVR12 rate than those in the 12-week arm (40.0% vs 100.0%). All 4 HCV-1b relapses had a Y93H RAS frequency of >99% at posttreatment week 12. Conclusions: Twelve weeks of grazoprevir/elbasvir therapy is highly effective for treatment-naive patients with mild fibrosis. A truncated, 8-week grazoprevir/elbasvir regimen might be applied for those with low viral loads or without a significant NS5A RAS frequency. Clinical trials registration: NCT03186365. Abstract : Twelve weeks of grazoprevir/elbasvir is highly effective for hepatitis C virus-1b treatment naïve patients with mild fibrosis. A truncated 8-week regimen might be applied for those with low viral loads or without significant nonstructural 5A mutants.